Effect of a slime knee poultice on knee pain relief in osteoarthritis patients attending the Thai Traditional Medicine Clinic at Phra Ajarn Mun Bhuridatto Hospital, Sakon Nakhon Province - Intase, Sunisa; Pongnaratorn, Panicha; Sirisin, Juthathip; Jitcharoentham, Anunkaorn; Chan-ae, Pensiri (Health Science, Science and Technology Reviews, 2025)
Knee osteoarthritis was important problem in middle age and elderly people, which caused cartilage degeneration of knee, leading to structure of joint abnormalities. Pain relief in the field of Thai traditional medicine used herbal poultices, however the method had complex process and the problem of stained clothes. The researcher applied slime poultices. The objective of this research was to compare before and after average knee pain of the effectiveness of slime poultices in knee osteoarthritis patients to admitted in Thai traditional medicine clinic, Phra Ajarn Mun Bhuridatto Hospital. The sample consisted of 44 knee osteoarthritis patients. Research instruments include the data record of patients, the VAS scale assessment and Oxford Knee Score assessment. The samples were passed the inclusion criteria, who received slime poultices of knee 15 minutes. These methods are used 1 time/day for 3 days, every other day: Monday, Wednesday, Friday and received poultices of knee 15 minutes. The results of research were statistically analyzed with SPSS Statistics ver.27, using Paired Simple T-test. The result was found that after experiments using slime poultices: the experiment group had average score of Knee Score represented 29.64+4.46 score, which was higher than before experiment. The compare of average level of severity of Knee osteoarthritis before and after experiment was found that the average score after experiment was high level, pain score was decreased statistically significant at p<0.05 and found that the effectiveness of slime poultices had average of pain score was decreased, when compared with before experiment statistically significant at p<0.05. The different average pain scores of left knee joint, right knee joint and both sides were 1.86 scores, 1.78 scores, 1.93 scores, respectively. Slime poultice could apply with treatment and people have another option for basic health care of themselves.